Model Edukasi Thaharah Melalui Teori dan Prakterk Wudhu’ bagi Anak-Anak MDTA di Desa Manambin - Fatimah Sahara; Anisah; Bungsu Nur Jadidah Nst; Wanni Nur Jannah; Rezky Hasyim Syah; Suci Rahmadani; Risna Suhro; Mhd. Bangsawan Nasution; Roy Rizky Pulungan; Edi Marjan Nasution (Sujud: Jurnal Agama, Sosial dan Budaya, 2025)
Thaharah (ritual purification) is an essential aspect of Islamic jurisprudence that covers purification from both physical and spiritual impurities. Without thaharah, worship cannot be considered valid. However, observations in Manambin Village show that many children still do not fully understand the correct procedures of thaharah, especially wudhu, according to Islamic law. This study aims to describe the educational model of thaharah through theoretical explanation and practical application of wudhu for elementary school children at MDTA Manambin. The research employed a descriptive qualitative approach, with data collected through participatory observation, semi-structured interviews, and documentation. Data analysis used Miles and Huberman’s model, consisting of data reduction, data display, and conclusion drawing. The educational program was conducted in four sessions: two sessions of theoretical explanation, one session of demonstration, and one session of direct practice by the participants. The findings reveal that the integration of theory and practice significantly improved the children’s understanding of thaharah and their skills in performing wudhu properly. Therefore, this educational model is effective in fostering awareness of the importance of cleanliness and in habituating children to perform worship correctly according to Islamic teachings. Furthermore, this study emphasizes that the approach to thaharah education, which integrates theory, demonstration, and direct practice, not only enhances children’s cognitive knowledge but also trains their psychomotor skills in performing worship. This applicative learning process is able to provide real experiences, so that children do not merely know about wudhu, but also become accustomed to performing it correctly.The findings show that thaharah education has a broader dimension than merely being a prerequisite for valid worship. Thaharah also serves as a means of shaping religious character, discipline, as well as a clean and healthy lifestyle. Thus, this educational model is relevant to be applied not only in MDTA Desa Manambin but also in other Islamic educational institutions.nThis study also contributes to the development of practical fiqh learning methods that are in line with the spirit of the Merdeka Curriculum, which emphasizes experiential learning and the formation of the Pancasila Student Profile. With consistent implementation, it is expected that children will grow into a generation of Muslims who not only understand the laws of fiqh but are also able to practice them in their daily lives with steadfastness.